Examining the geometry, age and genesis of buried Quaternary valley systems in the Midland Valley of Scotland, UK. (11th December 2018) - Kearsey, Timothy I.; Lee, Jonathan R.; Finlayson, Andrew; Garcia‐Bajo, Marieta; Irving, Anthony A. M.
Abstract : Buried palaeo‐valley systems have been identified widely beneath lowland parts of the UK including eastern England, central England, south Wales and the North Sea. In the Midland Valley of Scotland palaeo‐valleys have been identified yet the age and genesis of these enigmatic features remain poorly understood. This study utilizes a digital data set of over 100 000 boreholes that penetrate the full thickness of deposits in the Midland Valley of Scotland. It identified 18 buried palaeo‐valleys, which range from 4 to 36 km in length and 24 to 162 m in depth. Geometric analysis has revealed four distinct valley morphologies, which were formed by different subglacial and subaerial processes. Some palaeo‐valleys cross‐cut each other with the deepest features aligning east–west. These east–west features align with the reconstructed ice‐flow direction under maximum conditions of the Main Late Devensian glaciation. The shallower features appear more aligned to ice‐flow direction during ice‐sheet retreat, and were therefore probably incised under more restricted ice‐sheet configurations. The bedrock lithology influences and enhances the position and depth of palaeo‐valleys in this lowland glacial terrain. Faults have juxtaposed Palaeozoic sedimentary and igneous rocks and the deepest palaeo‐valleys occur immediately down‐ice of knick‐points in the more resistant igneous bedrock. The features are regularly reused and the fills are dominated by glacial fluvial and glacial marine deposits. This suggests that the majority of infilling of the features happened during deglaciation and may be unrelated to the processes that cut them.